IL‐33 attenuates the development of experimental autoimmune uveitis. Issue 11 (18th October 2014) - Barbour, Mark; Allan, Debbie; Xu, Heping; Pei, Cheng; Chen, Mei; Niedbala, Wanda; Fukada, Sandra Y.; Besnard, Anne‐Galle; Alves‐Filho, Jose C.; Tong, Xiaoguang; Forrester, John V.; Liew, Foo Yew; et al.
<x xml:space="preserve">Abstract</x> Interleukin‐33 (IL‐33) is associated with several important immune‐mediated disorders. However, its role in uveitis, an important eye inflammatory disease, is unknown. Here, we investigated the function of IL‐33 in the development of experimental autoimmune uveitis (EAU). IL‐33 and IL‐33 receptor (ST2) were expressed in murine retinal pigment epithelial (RPE) cells in culture, and IL‐33 increased the expression of Il33 and Mcp1 mRNA in RPE cells. In situ, IL‐33 was highly expressed in the inner nuclear cells of the retina of naïve mice, and its expression was elevated in EAU mice. ST2‐deficient mice developed exacerbated EAU compared with WT mice, and administration of IL‐33 to WT mice significantly reduced EAU severity. The attenuated EAU in IL‐33‐treated mice was accompanied by decreased frequency of IFN‐γ+ and IL‐17+ CD4+ T cells and reduced IFN‐γ and IL‐17 production but with increased frequency of IL‐5+ and IL‐4+ CD4 T cells and IL‐5 production in the draining lymph node and spleen. Macrophages from the IL‐33‐treated mice show a significantly higher polarization toward an alternatively activated macrophage phenotype. Our results therefore demonstrate that the endogenous IL‐33/ST2 pathway plays an important role in EAU, and suggest that IL‐33 represents a potential option for treatment of uveitis.